2021
DOI: 10.1002/art.41899
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Serum Protein Biomarkers That Differentiate Psoriatic Arthritis From Rheumatoid Arthritis

Abstract: Objective. To identify serum protein biomarkers that might distinguish patients with early inflammatory arthritis (IA) with psoriatic arthritis (PsA) from those with rheumatoid arthritis (RA) and may be used to support appropriate early intervention.Methods. The serum proteome of patients with PsA and patients with RA was interrogated using nano-liquid chromatography mass spectrometry (nano-LC-MS/MS) (n = 64 patients), an aptamer-based assay (SomaScan) targeting 1,129 proteins (n = 36 patients), and a multiple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Mc Ardle et al. ( 31 ) coupled cutting-edge serum proteomics with multivariate machine learning analyses to differentiate between patients suffering from psoriatic arthritis and those with rheumatoid arthritis. Different proteomics techniques were utilized: namely, nano-liquid chromatography mass spectrometry, SomaScan, an aptamer-based assays, and Luminex, a multiplexed antibody assay.…”
Section: Resultsmentioning
confidence: 99%
“…Mc Ardle et al. ( 31 ) coupled cutting-edge serum proteomics with multivariate machine learning analyses to differentiate between patients suffering from psoriatic arthritis and those with rheumatoid arthritis. Different proteomics techniques were utilized: namely, nano-liquid chromatography mass spectrometry, SomaScan, an aptamer-based assays, and Luminex, a multiplexed antibody assay.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics can be defined as the large-scale analysis of proteins. In the context of PsA, it has been applied mainly to identify biomarkers that can be detected in blood, synovial fluid or skin samples for the early diagnosis of PsA and its differentiation from psoriasis [ 47 , 48 , 49 ]. The proteome is much more complex and dynamic than the genome because there are an estimated ~20,000 protein-encoding genes in the human genome [ 50 ], but these give rise to multiple variants by alternative transcription, splicing and processing of RNA, post-translational modification and protein–protein interactions.…”
Section: Proteomicsmentioning
confidence: 99%
“…Most of the biomarker candidates are proposed for the detection of PsA [ 61 , 62 ], differentiation between mild and severe forms [ 63 , 64 ], measuring disease activity [ 65 ], or predicting which psoriasis patients are likely to develop PsA [ 66 ]. However, others have been proposed to distinguish PsA from other arthritic diseases such as RA [ 49 , 67 ] or to monitor responses to therapy [ 68 , 69 , 70 , 71 ]. For example, the label-free MS analysis of synovial fluid from PsA patients revealed 12 candidate PsA markers including the injury marker MMP3, as well as the inflammatory proteins S100A9 and CRP [ 62 ].…”
Section: Proteomicsmentioning
confidence: 99%
“…This increase in LRG is associated with a relatively higher level of IL-6 in RA compared to SpA, which in turn produced a greater increase in LRG expression. 17 Nakajima et al, found that serum LRG levels were also elevated in patients with PsA compared to patients with psoriasis vulgaris. 23 Currently, there are no existing studies comparing LRG values in RA and SpA patients using blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the administration of drugs targeting the interleukin (IL)-12/IL-23 and IL-17 pathways have proven beneficial in PsA, but not in RA. 17,18 In some cases, RA and SpA may show clinical symptoms that are difficult to distinguish from one another. Therefore, an examination to assist the diagnosis of RA and SpA is warranted.…”
Section: Introductionmentioning
confidence: 99%